Carbon nanoparticle composite material taking polyether-ether-ketone as base material and application of carbon nanoparticle composite material

By using polyether ether ketone substrate in the bearing, composite materials with glass fiber and carbon nanomaterials are formed to form composite materials with excellent insulation properties and improved mechanical properties, the electrical corrosion problem caused by leakage current is solved and the electrical insulation of the bearing is realized Double improvement and mechanical performance.

CN119264598APending Publication Date: 2025-01-07AB SKF SKF PATENT DEPARTMENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310809224.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively curb electrical corrosion caused by leakage current in bearings. The high dielectric constant of the ceramic insulating coating leads to a high capacitance value. The lack of mechanical properties of polymer insulating coatings is unable to meet the dual requirements of electrical insulation and mechanical properties.

Method used

Polyether ether ketone (PEEK) is used as the substrate, and 30±20% glass fiber, 0.1~2.0% graphene and/or 0.1~2.0% carbon nanotubes are added to form a composite material to improve mechanical strength. Impact resistance and thermal conductivity significantly improve the insulation and mechanical properties of the material.

Benefits of technology

The electrical insulating layer formed by the composite material can significantly weaken leakage current, suppress electrical corrosion, improve the mechanical and heat dissipation performance of the bearing, meet the dual requirements of electrical insulation and mechanical properties, and provide an effective solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264598A_ABST
    Figure CN119264598A_ABST
Patent Text Reader

Abstract

The invention relates to a composite material taking polyether-ether-ketone as a base material. The composite material comprises the following components in percentage by weight: 30 + / -20 percent of glass fiber, 0.1-2.0 percent of graphene and / or 0.1-2.0 percent of carbon nano tube. On the basis of the composite material, the invention also provides an electric insulation bearing ring (2, 3) and an electric insulation rolling bearing (1) adopting the electric insulation bearing ring. The electrically insulating bearing ring (2, 3) comprises an electrically insulating layer formed from the above composite material for blocking the passage of a leakage current. The electric insulation layer formed by the polymer composite material can greatly weaken the leakage current of the electric insulation bearing and obviously inhibit the electric corrosion damage to the bearing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a carbon nanoparticle composite material with polyetheretherketone as a substrate, and in particular to the application of the composite material in the field of bearings. Background Art

[0002] During the design, manufacturing or installation of the motor, deviations in the distribution of magnetic poles or the position of the shaft will lead to an asymmetric magnetic field. When the magnetic flux alternates between symmetry and asymmetry, it will cause the motor shaft to cut the magnetic lines of force during rotation, thereby forming an induced electromotive force. This induced electromotive force acts between the shaft and the housing, forming a "shaft voltage" that is applied to the inner and outer rings of the bearing. When the amplitude of the shaft voltage is sufficient to break through the lubricating oil film, the current will pass through the outer ring, oil film and inner ring of the bearing to form a "shaft current" (also known as "leakage current"). The leakage current that causes the oil film to discharge will form micro pitting pits on the surface of the bearing raceway. This phenomenon is called "electrocorrosion". Even if the current intensity is relatively weak, the electrocorrosion phenomenon still exists.

[0003] The traditional method of blocking leakage current is to provide an electrical insulation coating on the radial surface of the bearing ring (typically the outer surface of the outer ring and / or the inner surface of the inner ring). The traditional electrical insulation coating mainly uses ceramic materials, which usually contain aluminum oxide and are formed on the above-mentioned surface of the bearing ring by plasma spraying. Although ceramics are insulating materials, their relative dielectric constant is usually between 8.5 and 10, which is a polar or even strongly polar dielectric material. If the inner and outer rings of the bearing can be regarded as a parallel plate capacitor, then according to the formula C=εS / d (where C is the capacitance value of the parallel plate capacitor, ε is the dielectric constant of the medium between the plates, S is the area of ​​the plates, and d is the distance between the plates), ceramic materials with higher dielectric constants will result in higher capacitance values ​​for the bearing. This means that, especially under the action of high-frequency shaft voltage, the leakage current will reach a high level, and the electrical corrosion effect on the bearing should not be underestimated. In addition, the plasma spraying process will inevitably leave material pores on the ceramic coating, so an additional sealing process is required to seal the pores to prevent these pores from retaining moisture in a humid environment and reducing the electrical insulation performance of the coating. The sealing process further increases the manufacturing cost of the ceramic coating.

[0004] To solve the above problems, the latest technology attempts to use polymers as the composition material of the insulating coating, especially polymers with a relative dielectric constant between 3.0 and 3.5. The average dielectric constant of these polymers is about 1 / 3 of that of ceramics, so the capacitance value is also 1 / 3 of the latter accordingly. Since the capacitive impedance is inversely proportional to the capacitance value, the polymer coating can make the capacitive impedance of the insulating bearing reach an average of three times that of the ceramic coating. Without considering other factors, the multiplied capacitive impedance can greatly reduce the leakage current of the bearing, thereby significantly inhibiting the electrical corrosion damage suffered by the bearing.

[0005] However, compared with metal materials, a significant weakness of polymers is their poor mechanical strength and thermal conductivity. The above weaknesses greatly limit the application of polymers in the field of machinery (especially bearings). Reality calls for a polymer composite material that can effectively curb leakage current and have improved mechanical properties. Summary of the invention

[0006] To solve the above technical problems, the present invention provides a composite material based on polyetheretherketone, comprising the following components in percentage: 30±20wt% of glass fiber, 0.1-2.0wt% of graphene and / or 0.1-2.0wt% of carbon nanotubes.

[0007] Among the above materials, glass fiber can improve the comprehensive mechanical strength of the material, graphene can improve the impact resistance (toughness) and thermal conductivity of the material, and CNT can comprehensively improve the strength and rigidity of the composite material. The composite material of the above ingredients is a new material derived from experiments that has both excellent insulation properties and improved mechanical properties. It has been proven that it can significantly curb leakage current, thus providing an effective solution to the problem of electrical corrosion of bearings.

[0008] Based on the above materials, the present invention also provides an electrically insulating bearing ring. The electrically insulating layer formed by the above composite material enables the rolling bearing to have not only a dielectric constant at the polymer level, but also significantly improved mechanical properties and heat dissipation performance, thereby meeting the dual requirements of the rolling bearing in terms of electrical insulation and mechanical properties.

[0009] Various embodiments and beneficial technical effects of the present invention are described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 A graph showing the measured distribution of dielectric constants of the composite material based on PEEK in different embodiments of the present invention; and

[0011] Figure 2 Schematic diagram showing the partial structure of an electrically insulating rolling bearing and its electrically insulating layer. DETAILED DESCRIPTION

[0012] In the following description, the same or similar reference numerals are always used to indicate the same or similar components. In addition, the terms indicating directions, such as "axial", "radial" and "circumferential direction", refer to the axial, radial and circumferential directions of the components being described unless otherwise limited or specified.

[0013] As a polymer, polyetheretherketone (PEEK) has both rigidity and flexibility, and its fatigue resistance under alternating stress is particularly outstanding. It still has good electrical insulation properties even at very high temperatures, and the dielectric loss under high frequency conditions is very small. The above properties make it particularly suitable as an insulating layer material for electrically insulating bearings. Therefore, the present invention uses PEEK as a substrate and further improves its mechanical strength by adding glass fiber (Glass Fiber, abbreviated GF). Glass fiber is an inorganic non-metallic material with excellent performance, characterized by high specific strength (specific strength), which can reach several times that of low carbon steel. In the present invention, the content of glass fiber can be between 10 and 50wt% according to the needs of the application (for example, mechanical strength), preferably between 10 and 30wt%, and more preferably between 10 and 20wt%.

[0014] In addition, the present invention further improves the physical and chemical properties of the material by adding graphene and / or carbon nanotubes (Carbon Nanotubes, abbreviated CNT) to PEEK. In the experiment, the graphene used is graphene nanoplatelets (Graphene Nanoplatelets, abbreviated GNP), also known as graphene nanosheets (Graphene Nanosheets, abbreviated GNS) or carbon nanosheets (Carbon Nanoflakes, abbreviated CNF), which are two-dimensional graphite nanomaterials with a thickness of nanometers, and in extreme cases can also be single-layer graphene. The carbon nanotubes used in the present invention can be single-walled nanotubes, double-walled nanotubes and / or multi-walled nanotubes. The following describes in detail some of the striking material properties exhibited by the present invention during the experiment through specific embodiments.

[0015] Example 1: PEEK is used as the base material, and the composite material contains 15wt% GF;

[0016] Example 2: PEEK is used as the substrate, and the composite material contains 15wt% GF and 0.2wt% GNP;

[0017] Example 3: PEEK is used as the substrate, and the composite material contains 15wt% GF and 0.4wt% GNP;

[0018] Example 4: PEEK is used as the base material, and the composite material contains 15 wt% GF and 0.2 wt% CNT.

[0019] Table 1

[0020]

[0021] Table 1 contains the measured values ​​of the mechanical properties of composite materials based on PEEK under different embodiments. It can be seen from Table 1 that the addition of CNT, even in trace amounts (0.2wt%), can comprehensively improve the mechanical properties of the material, especially the deformation resistance (i.e., rigidity), including tensile strength, tensile modulus, flexural strength, flexural modulus, and flexural elongation at break. Among them, the increase in flexural modulus is the most significant. Compared with the case where only GF is added, the strength of the material after adding CNT increases from 5916Mpa to 6949Mpa, an increase of 17%. According to the needs of the application, the content of CNT can be further adjusted, and the preferred range can be between 0.1 and 2.0wt%, further between 0.1 and 1.0wt%, and further between 0.1 and 0.5wt%, until between 0.1 and 0.3wt%.

[0022] In addition, it can be seen from Table 1 that although the addition of GNPs is not helpful for improving the deformation resistance of the material, it can significantly improve the impact resistance (i.e., toughness) of the material. From this perspective, the content of GNPs is not constant, for example, it can be between 0.1 and 2.0 wt%, further between 0.1 and 1.0 wt%, further between 0.1 and 0.5 wt%, and even between 0.3 and 0.5 wt%. However, it can be seen from the comparison of Example 2 and Example 3 that the effect of 0.2 wt% of GNPs in improving the simply supported beam impact strength exceeds that of 0.4 wt% of GNPs, suggesting that the content of GNPs near 0.2 wt% may reach a peak value of material toughness (although it may be a regional peak value).

[0023] Figure 1 The dielectric constant ε of the composite material based on PEEK in different embodiments r Although Table 1 shows that 0.2wt% GNP can make the impact strength (toughness) of the material reach a peak value, Figure 1 It shows that this content of GNPs makes the dielectric constant ε r The result is that the capacitance of the bearing with the material as the electrical insulation layer increases, which is not conducive to eliminating the electrical corrosion effect of the bearing. In contrast, 0.4wt% GNP or 0.2wt% CNT has no significant effect on improving the dielectric constant of the material, which to some extent eliminates the inventor's previous concerns that carbon nanomaterials will significantly increase the conductivity of the material.

[0024] Table 2

[0025]

[0026] Table 2 shows the measured values ​​of thermal conductivity of the composite materials of different embodiments at different temperatures. It can be seen from the table that 0.4wt% of GNP in Example 3 can increase the thermal conductivity of the material by about 30% compared with other embodiments. This is very beneficial for bearing applications, because good heat dissipation performance is a prerequisite for reliable operation of bearings.

[0027] Various embodiments of composite materials with improved performance by adding different types and amounts of carbon nanomaterials to PEEK are described above. It can be seen that the material in Example 3 (PEEK 15GF 0.4GNP) has comprehensive advantages in impact resistance (toughness), dielectric constant and heat dissipation performance, and the material in Example 4 (PEEK 15GF0.2CNT) has comprehensive advantages in deformation resistance (rigidity) and dielectric constant.

[0028] It is necessary to point out that, up to now, there is no experiment or literature to disclose the contradiction between graphene and carbon nanotubes in terms of material modification. On the contrary, it is theoretically proved that the stable structure of carbon nanotubes can provide good support for graphene, and the softness of graphene can provide advantages for filling the gaps of carbon nanotubes. Not only that, the synergistic effect between the two can also improve the thermal conductivity of the medium, so that the spatial structure and physicochemical properties of the two can be complemented. In view of this, in combination with Example 3 and Example 4, on the basis of adding GF in an applicable proportion (including but not limited to 15wt%) to PEEK, by adding 0.4wt% of GNP and 0.2wt% of CNT to the material at the same time, the material can be made to have advantages in many aspects such as deformation resistance, toughness, dielectric constant and heat dissipation performance at the same time, thereby achieving the best solution in a comprehensive sense. As a preferred embodiment, the technical solution can be summarized as comprising 15±5wt% of glass fiber, 0.4±0.1wt% of graphene and 0.2±0.1wt% of carbon nanotubes.

[0029] Figure 2A schematic diagram of the partial structure of a rolling bearing using the composite material as an electrical insulation layer is shown. Taking a ball bearing as an example, the rolling bearing 1 comprises an inner ring 2, an outer ring 3, and at least one row of rolling elements 4 arranged between the inner ring raceway 24 and the outer ring raceway 34. Unlike a non-insulated bearing, an insulating coating for blocking the passage of current is formed on the corresponding surfaces of the inner ring 2 and / or the outer ring 3 of the insulating bearing 1. In the specific embodiment shown in the figure, the insulating coating can be formed on the inner surface 21 of the inner ring 2, or on the outer surface 31 of the outer ring 3. In addition, the insulating coating can also be further formed on the end faces 22 on both sides of the axial direction of the bearing inner ring 2 and / or the end faces 32 on both sides of the axial direction of the bearing outer ring 3. In principle, the insulating coating can be formed on all surfaces of the bearing inner ring 2 and the outer ring 3 except the raceways 24 and 34, and even on the respective surfaces of the shoulders 23 on both sides of the inner ring raceway 24 and the shoulders 33 on both sides of the outer ring raceway 34. In the description of the present invention, all the above-mentioned surfaces of the bearing ring that can be coated with an insulating coating to prevent leakage current from passing through the rolling bearing are referred to as "corresponding surfaces".

[0030] In summary, by adding glass fibers and carbon nanomaterials, the present invention successfully achieves the "directional" modification of PEEK. On the basis of the lower dielectric constant of PEEK (relative to ceramics), the addition of glass fibers and carbon nanomaterials has produced a comprehensive improvement in the mechanical properties of the material. The electrical insulation layer formed by this material can greatly reduce the leakage current of the bearing and significantly inhibit the electrical corrosion damage suffered by the bearing. In addition, this material can also be formed on any surface of the bearing ring by injection molding or spraying, with a minimum thickness of 10 microns. The thin insulating layer has little effect on the size of the bearing and can perfectly replace existing non-insulated bearings.

[0031] Those skilled in the art should understand that the composite material and its application in the field of bearings are not limited by the specific implementation methods, and the more general technical solutions shall be subject to the limitations in the attached claims. Any changes and improvements to the present invention, as long as they comply with the limitations in the attached claims, shall fall within the scope of protection of the present invention.

Claims

1. A composite material based on polyetheretherketone, comprising the following components in percentage: 30±20wt% of glass fiber, 0.1-2.0wt% of graphene and / or 0.1-2.0wt% of carbon nanotubes.

2. The composite material according to claim 1, characterized in that: The composite material comprises 20±10 wt % of glass fiber, 0.1-1.0 wt % of graphene and / or 0.1-1.0 wt % of carbon nanotube.

3. The composite material according to claim 2, characterized in that: The composite material comprises 15±5wt% of glass fiber, 0.1-0.5wt% of graphene and / or 0.1-0.5wt% of carbon nanotube.

4. The composite material according to claim 3, characterized in that: The content of the graphene is 0.4±0.1wt%, and / or the content of the carbon nanotube is 0.2±0.1wt%.

5. The composite material according to any one of claims 1 to 4, characterized in that: The contents of the graphene and the carbon nanotubes are not zero at the same time.

6. An electrically insulating bearing ring (2, 3), comprising an electrically insulating layer formed on a corresponding surface of the bearing ring from the composite material according to any one of the preceding claims for preventing leakage current from passing therethrough.

7. A rolling bearing (1) comprising a bearing ring (2, 3) according to claim 6.